Construct Validity of the Mentalization Scale (MentS) Within a Mixed Psychiatric Sample - Richter, Felix; Steinmair, Dagmar; Löffler-Stastka, Henriette (Frontiers in Psychology, 2021)
Introduction: The concept of mentalizing is nowadays widely used in research as well as in clinical practice. Despite its popularity, the development of an economic assessment is still challenging. The Mentalization Scale appears to be a promising measurement with good psychometric properties but lacking convergent validity with the Reflective Functioning Scale. Objective: This study aims to test the construct validity of the Mentalization Scale through correlations with the gold standard, the Reflective Functioning Scale, within a clinical sample. Furthermore, it was of interest to replicate its internal consistency. Methods: Twenty-six inpatients of an acute psychiatric ward in Vienna were given the Mentalization Scale (MentS). They were interviewed with the Brief Reflective Function Interview, which was coded with the Reflective Functioning Scale. Correlations and internal consistency were calculated. Results: Concerning the primary aim of this study, the validity was satisfactory for the MentS whole-scale mentalizing as well as for the subscales self- and other-oriented mentalizing. Internal consistency was lower to the findings of the developer and close to the 0.70 threshold. Conclusion: Our findings could foster the psychometric properties of the MentS. Furthermore, the MentS seems to be a promising measurement tool for detecting different dimensions of reflective functioning. Limitations and further research are discussed.